2001
DOI: 10.1038/emm.2001.43
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging and antioxidant enzyme fortifying activities of extracts from Smilax china root

Abstract: The extract from Smilax china root has been used as medicinal remedy and reported to retain antimicrobial and antimutagenic acitivities. In this study, a possible presence of antioxidant activity of Smilax china root extract was investigated. Methanol extract (Me) revealed the presence of high 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity (IC 50 7.4 µg/ml) and protective property of cell's viability. Further fractionation with various solvent extraction and assay showed high levels of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 33 publications
1
39
0
3
Order By: Relevance
“…The EtOAc soluble fraction (6.9 g) was chromatographed on a Sephadex LH-20 column [4.0 × 68.0 cm (Pharmacia Biotech AB, Uppsala, Sweden); stepwise gradient of 50% to 100% methanol] to yield nineteen fractions (Fr. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. HPLC [µ-Bondapak C 18 , 7.8 × 300 mm (Waters, Milford, MA, USA); 1% acetic acid in 35% methanol; 1.5 ml / min] of Fr.…”
Section: Chemicalsmentioning
confidence: 99%
“…The EtOAc soluble fraction (6.9 g) was chromatographed on a Sephadex LH-20 column [4.0 × 68.0 cm (Pharmacia Biotech AB, Uppsala, Sweden); stepwise gradient of 50% to 100% methanol] to yield nineteen fractions (Fr. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. HPLC [µ-Bondapak C 18 , 7.8 × 300 mm (Waters, Milford, MA, USA); 1% acetic acid in 35% methanol; 1.5 ml / min] of Fr.…”
Section: Chemicalsmentioning
confidence: 99%
“…It has been shown that free radical scavengers and antioxidants are useful in protecting against cadmium toxicity [8]. Great efforts have been made in an attempt to find safe and potent natural antioxidants from plant sources [9]. Ocimum sanctum Linn.…”
Section: Introductionmentioning
confidence: 99%
“…The catalase (CAT) activity also showed significant (p<0.05) increase in hepatotoxic rats treated with varying dose of the extract compared with the hepatotoxic rats. Cellular radical scavenging systems include the enzymes such as SOD which scavenges the superoxide anions by catalyzing its dismutation and catalase (CAT) a haem enzyme which removes hydrogen peroxide [21]. Therefore, reduction in the activity of these enzymes (SOD and CAT) results in a number of deleterious effects due to the accumulation of superoxide anion and hydrogen peroxide.…”
Section: Effect Of Methanolic Extract Of Citulus Lanatus Seeds On Oximentioning
confidence: 99%